The Relationship Between Locus of Control and Religious Behavior and Beliefs in a Large Population of Parents: An Observational Study - Iles-Caven, Yasmin; Gregory, Steven; Ellis, Genette; Golding, Jean; Nowicki, Stephen (Frontiers in Psychology, 2020)
The purpose of the present study was to examine, in a large representative population, the association between self-reported religious beliefs, attitudes and behavior and locus of control of reinforcement as defined by Rotter. Results of previous research have failed to clearly determine what, if any, associations existed. In this study, analyses showed individuals with an internal locus of control were not only more likely to believe in a divine power, to admit a divine power helped them in the past, to ask for help from a divine power in the future, to attend places of worship more often than those who were external, but also that they were significantly more likely to maintain their religious beliefs and behaviors over a six year period compared to those with an external orientation. Additional exploratory analyses by gender revealed that compared to internal men, internal women were significantly higher in all indicators of religious belief and action except for attending church weekly and obtaining help from religious leaders where internal men were higher. The present findings support the association between the generalized expectancy of locus of control as defined by Rotter and religious beliefs, attitudes and behaviors.